Strategi Peningkatan Kinerja Penyuluh Pertanian dalam Pengembangan Agribisnis di Kabupaten Banyuwangi - Danang Sudarso Widya Prakoso Joyo Widakdo (Jurnal Penyuluhan, 2014)
Agribusiness development in Banyuwangi growing supported by the agricultural extension. The role of agricultural extension is needed by communities and farmers. Therefore, strategies are needed to improve its performance, especially with the implementation of the difference between the central government and local governments (regional autonomy). Research related to strategies for improving the performance of agricultural extension workers, especially in Banyuwangi has been done by first analyzing the factors that affect the performance of the extension, which is then analyzed more in depth with the IE method, SWOT and QSPM and eventually obtained agricultural extension strategies for improving performance. The results showed that the strength factor is the suitability of a high enough salary, weakness factor is the lack of monitoring of the performance of agricultural extension, chances are the interest factor be enough agricultural extension, the threat factor is the lack of agricultural extension PNS. Strategic priorities for performance improvement of agricultural extension is the need to evaluate the performance of agricultural extension monitoring periodically, the second priority is additional quota admission counselor civil servants, the third priority the strengthening of IT, the fourth priority intensification of agricultural extension training programs to improve the performance of the performance competencies of agricultural extension, the fifth priority the improvement of cooperation among government agencies to integrate all of the work program for the right target, and the sixth priority poktan role to participate in the establishment of monitoring the performance of agricultural extension. While the managerial implications in the development of agribusiness, there are three themes, namely human resource development extension agent, performance evaluation, and monitoring the performance of agricultural extension.Keywords: The performance of the agricultural instructor, Banyuwangi agribusiness development, strategic priorities,managerial, implication